Is Bank Financial Performance Affected By Corporate Social Responsibility? A Meta-Analysis - Mukhamad Sholikudin; Hwihanus Hwihanus (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study investigates the impact of Corporate Social Responsibility (CSR) on the Financial Performance of Banks. A meta-analysis of the previous five studies showed that CSR activities as a whole had a positive impact on CFP, especially on Return on Equity (ROE) and Net Interest Margin (NIM). However, the influence of CSR on Return on Assets (ROA) is inconsistent. These findings show that CSR can increase bank profitability, but the effect is not uniform across all aspects of financial performance. This research makes an important contribution by integrating the findings from various studies and highlighting the strategic role of CSR in increasing financial and non-financial added value in the banking industry. The practical implication is that banks need to formulate and implement effective CSR strategies to achieve sustainable long-term financial goals and meet stakeholder expectations.